2012
DOI: 10.7589/0090-3558-48.2.425
|View full text |Cite
|
Sign up to set email alerts
|

DETECTION OF PrPCWD IN FECES FROM NATURALLY EXPOSED ROCKY MOUNTAIN ELK (CERVUS ELAPHUS NELSONI) USING PROTEIN MISFOLDING CYCLIC AMPLIFICATION

Abstract: Chronic wasting disease (CWD) is a transmissible spongiform encephalopathy affecting captive and free-ranging cervids. Currently, tests for CWD in live animals involve relatively invasive procedures to collect lymphoid tissue biopsies and examine them for CWD-associated, protease-resistant cervid prion protein (PrP(CWD)) detected by immunohistochemistry (IHC). We adapted an ultrasensitive prion detection system, protein misfolding cyclic amplification (PMCA), to detect PrP(CWD) in Rocky Mountain elk (Cervus el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 28 publications
0
65
0
Order By: Relevance
“…5 Infected cervids have been reported to shed PrP TSE in bodily fluids, disseminating infectious prions in urine, feces, blood and saliva. [7][8][9][10] PrP TSE binds to whole soil and interaction with some soil minerals has been shown to increase the infectivity of PrP TSE . 11,12 Although PrP TSE binds to soil, it requires 60 d for CWD PrP TSE to become fully bound in sandy soil as compared with 30 d for prions associated with transmissible mink encephalopathy (TME).…”
Section: Introductionmentioning
confidence: 99%
“…5 Infected cervids have been reported to shed PrP TSE in bodily fluids, disseminating infectious prions in urine, feces, blood and saliva. [7][8][9][10] PrP TSE binds to whole soil and interaction with some soil minerals has been shown to increase the infectivity of PrP TSE . 11,12 Although PrP TSE binds to soil, it requires 60 d for CWD PrP TSE to become fully bound in sandy soil as compared with 30 d for prions associated with transmissible mink encephalopathy (TME).…”
Section: Introductionmentioning
confidence: 99%
“…These results could infer that IOME may preferentially bind prions from complex matrices, perhaps reducing potential assay inhibitors. We tested this theory on faeces, which has traditionally presented significant problems for in vitro prion-amplification assays (Pulford et al, 2012;Tamgüney et al, 2009). Despite higher false-positive rates compared with other excreta assayed, the IOME protocol resulted in a statistical significance difference between faecal samples from CWD-positive versus -negative deer.…”
Section: à10mentioning
confidence: 99%
“…Faecal samples have traditionally been difficult to assay by any method due to the complexity of the material present (Pulford et al, 2012;Krüger et al, 2009;Saborio et al, 2001). Blinded faecal samples from six CWD-positive and three CWDnegative deer were analysed, with or without IOME-RTQuIC.…”
Section: à10mentioning
confidence: 99%
“…Using amplification approaches, evidence of CWD prion presence has been reported in a range of bodily fluids (19,74,78,(89)(90)(91), making them tempting targets for the development of novel diagnostic strategies. Studies in other model systems, including sheep and humans, have identified peripheral tissues which may also serve as a useful diagnostic sample and indicator of central nervous system infection (92-94).…”
Section: Sample Selection For Antemortem Testingmentioning
confidence: 99%
“…to assess the potential for infectivity in body fluids and other excreta (19,74,78,79), and to detect low levels of misfolded protein in soil (80), water (81), and plant samples (82). Notably, the CWD seeds generated in vitro by sPMCA have proven infectious to some degree in susceptible hosts (83), indicating that the technique may accurately model what occurs in vivo; therein lays its advantage among amplification strategies.…”
Section: Protein Misfolding Cyclic Amplificationmentioning
confidence: 99%